2012
DOI: 10.1002/anie.201204505
|View full text |Cite
|
Sign up to set email alerts
|

α‐Selective Organocatalytic Synthesis of 2‐Deoxygalactosides

Abstract: Alpha rules: A thiourea acts as an efficient organocatalyst for the glycosylation of protected galactals to form oligosaccharides containing a 2-deoxymonosaccharide moiety. The reaction is highly stereoselective for α-linkages and proceeds by way of a syn-addition mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
140
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 56 publications
8
140
2
4
Order By: Relevance
“…90 The same thiourea has also been employed as a catalyst for the selective addition of alcohols to glycals resulting in the formation of 2-deoxy-α-glycosides, although in this instance it is considered to function merely as a mild protic acid. 91–92 In related work chiral binol-derived phosphoric acid catalysts have been employed to promote cyclization of 1-(γ-hydroxypropyl)glycals and their homologs to spiroketals. It was demonstrated that the anomeric selectivity of the reaction is dependent on the chirality of the catalyst, and cyclic hydrogen bonded transition state was invoked to explain the phenomenon.…”
Section: Counterion and Additive Effectsmentioning
confidence: 99%
“…90 The same thiourea has also been employed as a catalyst for the selective addition of alcohols to glycals resulting in the formation of 2-deoxy-α-glycosides, although in this instance it is considered to function merely as a mild protic acid. 91–92 In related work chiral binol-derived phosphoric acid catalysts have been employed to promote cyclization of 1-(γ-hydroxypropyl)glycals and their homologs to spiroketals. It was demonstrated that the anomeric selectivity of the reaction is dependent on the chirality of the catalyst, and cyclic hydrogen bonded transition state was invoked to explain the phenomenon.…”
Section: Counterion and Additive Effectsmentioning
confidence: 99%
“…To further explore the glycosylation properties of 6, we proceeded to examine thioglycosides 12 19 and 13 20 as acceptors. Reaction of 12 with donor 6 was conducted under the optimized conditions, and expectedly, the desired sialoside 20 was isolated in very high yield and moderate a/b 2:1 selectivity.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…By deploying 1 mol% of thiourea-derived catalyst 9 the authors succeeded in glycosylations of protected glycal 15. 2-Deoxyglycoside 17 was obtained with high yields (Scheme 4.6) [67,68].…”
mentioning
confidence: 99%